Discover new perspectives and gain insights with IDNLearn.com. Join our Q&A platform to receive prompt and accurate responses from knowledgeable professionals in various fields.
Sagot :
To determine which expression is a factor of the polynomial [tex]\(x^4 - x^3 - 11x^2 + 5x + 30\)[/tex], we can utilize the Factor Theorem. The Factor Theorem states that [tex]\(x-c\)[/tex] is a factor of a polynomial if and only if the value of the polynomial evaluated at [tex]\(c\)[/tex] is zero, i.e., [tex]\(P(c) = 0\)[/tex].
Let's denote the polynomial by [tex]\(P(x) = x^4 - x^3 - 11x^2 + 5x + 30\)[/tex].
We'll check each potential factor by evaluating the polynomial at specific values:
1. For [tex]\(x + 2\)[/tex], check if [tex]\(P(-2) = 0\)[/tex]:
[tex]\[ P(-2) = (-2)^4 - (-2)^3 - 11(-2)^2 + 5(-2) + 30 \][/tex]
[tex]\[ = 16 + 8 - 44 - 10 + 30 \][/tex]
[tex]\[ = 16 + 8 - 44 - 10 + 30 \][/tex]
[tex]\[ = 54 - 54 \][/tex]
[tex]\[ = 0 \][/tex]
Since [tex]\(P(-2) = 0\)[/tex], [tex]\(x + 2\)[/tex] is a factor of the polynomial.
2. For [tex]\(x - 2\)[/tex], check if [tex]\(P(2) = 0\)[/tex]:
[tex]\[ P(2) = 2^4 - 2^3 - 11(2)^2 + 5(2) + 30 \][/tex]
[tex]\[ = 16 - 8 - 44 + 10 + 30 \][/tex]
[tex]\[ = 48 - 52 \][/tex]
[tex]\[ = -4 \][/tex]
Since [tex]\(P(2) \neq 0\)[/tex], [tex]\(x - 2\)[/tex] is not a factor.
3. For [tex]\(x + 5\)[/tex], check if [tex]\(P(-5) = 0\)[/tex]:
[tex]\[ P(-5) = (-5)^4 - (-5)^3 - 11(-5)^2 + 5(-5) + 30 \][/tex]
[tex]\[ = 625 + 125 - 275 - 25 + 30 \][/tex]
[tex]\[ = 780 - 300 \][/tex]
[tex]\[ = 480 \][/tex]
Since [tex]\(P(-5) \neq 0\)[/tex], [tex]\(x + 5\)[/tex] is not a factor.
4. For [tex]\(x - 5\)[/tex], check if [tex]\(P(5) = 0\)[/tex]:
[tex]\[ P(5) = 5^4 - 5^3 - 11(5)^2 + 5(5) + 30 \][/tex]
[tex]\[ = 625 - 125 - 275 + 25 + 30 \][/tex]
[tex]\[ = 655 - 400 \][/tex]
[tex]\[ = 255 \][/tex]
Since [tex]\(P(5) \neq 0\)[/tex], [tex]\(x - 5\)[/tex] is not a factor.
Based on our evaluations, the correct factor of [tex]\(x^4 - x^3 - 11x^2 + 5x + 30\)[/tex] is:
(1) [tex]\(x + 2\)[/tex]
Let's denote the polynomial by [tex]\(P(x) = x^4 - x^3 - 11x^2 + 5x + 30\)[/tex].
We'll check each potential factor by evaluating the polynomial at specific values:
1. For [tex]\(x + 2\)[/tex], check if [tex]\(P(-2) = 0\)[/tex]:
[tex]\[ P(-2) = (-2)^4 - (-2)^3 - 11(-2)^2 + 5(-2) + 30 \][/tex]
[tex]\[ = 16 + 8 - 44 - 10 + 30 \][/tex]
[tex]\[ = 16 + 8 - 44 - 10 + 30 \][/tex]
[tex]\[ = 54 - 54 \][/tex]
[tex]\[ = 0 \][/tex]
Since [tex]\(P(-2) = 0\)[/tex], [tex]\(x + 2\)[/tex] is a factor of the polynomial.
2. For [tex]\(x - 2\)[/tex], check if [tex]\(P(2) = 0\)[/tex]:
[tex]\[ P(2) = 2^4 - 2^3 - 11(2)^2 + 5(2) + 30 \][/tex]
[tex]\[ = 16 - 8 - 44 + 10 + 30 \][/tex]
[tex]\[ = 48 - 52 \][/tex]
[tex]\[ = -4 \][/tex]
Since [tex]\(P(2) \neq 0\)[/tex], [tex]\(x - 2\)[/tex] is not a factor.
3. For [tex]\(x + 5\)[/tex], check if [tex]\(P(-5) = 0\)[/tex]:
[tex]\[ P(-5) = (-5)^4 - (-5)^3 - 11(-5)^2 + 5(-5) + 30 \][/tex]
[tex]\[ = 625 + 125 - 275 - 25 + 30 \][/tex]
[tex]\[ = 780 - 300 \][/tex]
[tex]\[ = 480 \][/tex]
Since [tex]\(P(-5) \neq 0\)[/tex], [tex]\(x + 5\)[/tex] is not a factor.
4. For [tex]\(x - 5\)[/tex], check if [tex]\(P(5) = 0\)[/tex]:
[tex]\[ P(5) = 5^4 - 5^3 - 11(5)^2 + 5(5) + 30 \][/tex]
[tex]\[ = 625 - 125 - 275 + 25 + 30 \][/tex]
[tex]\[ = 655 - 400 \][/tex]
[tex]\[ = 255 \][/tex]
Since [tex]\(P(5) \neq 0\)[/tex], [tex]\(x - 5\)[/tex] is not a factor.
Based on our evaluations, the correct factor of [tex]\(x^4 - x^3 - 11x^2 + 5x + 30\)[/tex] is:
(1) [tex]\(x + 2\)[/tex]
We appreciate your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. IDNLearn.com is dedicated to providing accurate answers. Thank you for visiting, and see you next time for more solutions.